Get the answers you need at Westonci.ca, where our expert community is always ready to help with accurate information. Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Answer:
Step-by-step explanation:
Simplifying
(7a + -2b) + -1[2(3a + -1c) + -3(2b + -3c)] = 0
Remove parenthesis around (7a + -2b)
7a + -2b + -1[2(3a + -1c) + -3(2b + -3c)] = 0
7a + -2b + -1[(3a * 2 + -1c * 2) + -3(2b + -3c)] = 0
7a + -2b + -1[(6a + -2c) + -3(2b + -3c)] = 0
7a + -2b + -1[6a + -2c + (2b * -3 + -3c * -3)] = 0
7a + -2b + -1[6a + -2c + (-6b + 9c)] = 0
Reorder the terms:
7a + -2b + -1[6a + -6b + -2c + 9c] = 0
Combine like terms: -2c + 9c = 7c
7a + -2b + -1[6a + -6b + 7c] = 0
7a + -2b + [6a * -1 + -6b * -1 + 7c * -1] = 0
7a + -2b + [-6a + 6b + -7c] = 0
Reorder the terms:
7a + -6a + -2b + 6b + -7c = 0
Combine like terms: 7a + -6a = 1a
1a + -2b + 6b + -7c = 0
Combine like terms: -2b + 6b = 4b
1a + 4b + -7c = 0
Solving
1a + 4b + -7c = 0
Solving for variable 'a'.
Move all terms containing a to the left, all other terms to the right.
Add '-4b' to each side of the equation.
1a + 4b + -4b + -7c = 0 + -4b
Combine like terms: 4b + -4b = 0
1a + 0 + -7c = 0 + -4b
1a + -7c = 0 + -4b
Remove the zero:
1a + -7c = -4b
Add '7c' to each side of the equation.
1a + -7c + 7c = -4b + 7c
Combine like terms: -7c + 7c = 0
1a + 0 = -4b + 7c
1a = -4b + 7c
Divide each side by '1'.
a = -4b + 7c
Simplifying
a = -4b + 7c
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.